Respon Pelaku Usaha Mikro, Kecil Dan Menengah (Umkm) Kemasan Pangan Terhadap Kewajiban Sertifikasi Halal Di Indonesia - Atsiriyyah, Annisa; Fitriyanti, Fadia (UI Scholars Hub, 2023)
This research aims to find out how Micro, Small and Medium Enterprises respond to packaged food towards the Halal Certification Obligation in Indonesia. This research uses a type of normative juridical research. The results of this research show that first, the response of packaged food MSMEs regarding the understanding of halal certification has been partially understood, although the details have not been conveyed. Second, the response of MSMEs to the JPH Law shows that they strongly agree with the existence of halal certification which is required by regulations to obtain a halal guarantee for a food product served. Third, the response of MSMEs to the benefits of halal certification labeling provides good value because in the future MSMEs want halal certification to be able to bring material benefits as well as benevolent (spiritual) values. Therefore, it is hoped that this latest law can be a solution to the various problems that arise and obstacles faced by MSMEs.